Probing the Ca2+-assisted π–π interaction during Ca2+-dependent protein folding. Issue 2 (22nd October 2015) - Matyska Liskova, Petra; Fiser, Radovan; Macek, Pavel; Chmelik, Josef; Sykora, Jan; Bednarova, Lucie; Konopasek, Ivo; Bumba, Ladislav
Abstract : A self-processing module of the iron-regulated protein FrpC of Neisseria meningitidis serves as an excellent experimental model for the investigation of the Ca 2+ -assisted π–π interaction during Ca 2+ -induced protein folding. Abstract : Protein folding is governed by a balance of non-covalent interactions, of which cation–π and π–π play important roles. Theoretical calculations revealed a strong cooperativity between cation–π involving alkali and alkaline earth metal ions and π–π interactions, but however, no experimental evidence was provided in this regard. Here, we characterized a Ca 2+ -binding self-processing module (SPM), which mediates a highly-specific Ca 2+ -dependent autocatalytic processing of iron-regulated protein FrpC secreted by the pathogenic Gram-negative bacterium Neisseria meningitidis . The SPM undergoes a Ca 2+ -induced transition from an intrinsically unstructured conformation to the compact protein fold that is ultimately stabilized by the π–π interaction between two unique tryptophan residues arranged in the T-shaped orientation. Moreover, the pair of tryptophans is located in a close vicinity of a calcium-binding site, suggesting the involvement of a Ca 2+ -assisted π–π interaction in the stabilization of the tertiary structure of the SPM. This makes the SPM an excellent model for the investigation of the Ca 2+ -assisted π–π interaction during Ca 2+ -induced protein folding.